\(x^2-2x+5+y^2-4y=0\)
\(x^2-2\times x\times1+1^2-1^2+y^2-2\times y\times2+2^2-2^2+5=0\)
\(\left(x-1\right)^2+\left(y-2\right)^2=0\)
\(\left(x-1\right)^2\ge0\)
\(\left(y-2\right)^2\ge0\)
\(\Rightarrow\left(x-1\right)^2+\left(y-2\right)^2=0\)
\(\Leftrightarrow\left(x-1\right)^2=\left(y-2\right)^2=0\)
\(\Leftrightarrow x-1=y-2=0\)
\(\Leftrightarrow x=1;y=2\)
\(x^2+4y^2+13-6x-8y=0\)
\(\Leftrightarrow x^2-6x+9+4y^2-8y+4=0\)
\(\Leftrightarrow\left(x-3\right)^2+\left(2y-2\right)^2=0\)
Dấu = xảy ra khi
\(\orbr{\begin{cases}x-3=0\\2y-2=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=3\\y=1\end{cases}}\)
1) x2 - 2x + 5 + y2 - 4y = 0
<=> x2 - 2x + 1 + y2 - 4y + 4 = 0
<=> ( x - 1 )2 + ( y - 2 )2 = 0
<=> \(\hept{\begin{cases}x-1=0\\y-2=0\end{cases}}\Leftrightarrow\hept{\begin{cases}x=1\\y=2\end{cases}}\)
2) x2 + 4y2 + 13 - 6x - 8y = 0
<=> x2 - 6x + 9 + 4y2 - 8y + 4 = 0
<=> ( x - 3 )2 + ( 2y - 2 )2 = 0
<=> \(\hept{\begin{cases}x-3=0\\2y-2=0\end{cases}}\Leftrightarrow\hept{\begin{cases}x=3\\y=1\end{cases}}\)
3) x2 + y2 + 6x - 10y + 34 = 0
<=> x2 + 6x + 9 + y2 - 10y + 25 = 0
<=> ( x + 3 )2 + ( y - 5 )2 = 0
<=> \(\hept{\begin{cases}x+3=0\\y-5=0\end{cases}}\Leftrightarrow\hept{\begin{cases}x=-3\\y=5\end{cases}}\)